Indications for implant removal: a prospective study - Jain, R. K.; Patel, Yogesh; Jayaswal, Abhijeet; Verma, Abhineet (International Journal of Research in Orthopaedics, 2019)
Background: The implants removal after fracture healing has always been an issue of controversy. After union, the implant ceases to be important and can be removed. Nevertheless, some patients require metallic implant removal due to various implant-related difficulties. Our study was aimed to identify the most common causes for removal of implant. Methods: The patients admitted for implant removal in our department were consented and included in the study. Pre-operative radiological images collected and evaluated. Post-operatively, images were taken and followed for resolution of symptoms or appearance of new problems. Results: A total of 60 patients were studied. Of these, 47 were males and 13 were females. Mean age was 33.7 years (range 4-70 years). Patient request (35% of patients) was the main indication for removal of implants. Reasons were found to be discomfort due to implant, infection, failure of implants and others. Conclusions: Belief regarding hardware removal has been set and most of them are agreed that routine removal should not be performed unless obviously indicated. In our attempt to fill this gap, we trust that routine removal should not be performed in ‘asymptomatic’ patients. The procedure should not need a big procedure than the implant fixation surgery. Procedure should be sought also as a risk like refracture, bleeding, infection, neurovascular injury and prior to surgery, proper consent to be taken and patient should be well explained. Sometimes indicated results expected after surgery can’t be fulfilled, and instead, complication can results.